2013
DOI: 10.2147/sar.s43684
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure among young adults in a developing country – a Jordanian case

Abstract: Secondhand smoke (SHS) exposure is a potentially preventable environmental pollutant that remains a major global public health concern. A descriptive cross-sectional design was used to assess secondhand smoke exposure, knowledge, attitudes, and avoidance behaviors, as well as policy agreements related to SHS among young adult university students in the northern part of Jordan. A convenience sample of 800 university students from three public universities participated in the present study. They completed four q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…These role models should advise patients to quit smoking and to avoid smoking in public places and in houses. This is important as passive smoking is also dangerous to nonsmoking individuals (19), and because anti-smoking policies are not enforced in public places and smoking is not banned inside houses in Jordan (9). Our results show that most healthcare professionals believe that smoking is harmful to health but their beliefs about the risks of smoking are significantly dependent on their smoking status.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These role models should advise patients to quit smoking and to avoid smoking in public places and in houses. This is important as passive smoking is also dangerous to nonsmoking individuals (19), and because anti-smoking policies are not enforced in public places and smoking is not banned inside houses in Jordan (9). Our results show that most healthcare professionals believe that smoking is harmful to health but their beliefs about the risks of smoking are significantly dependent on their smoking status.…”
Section: Discussionmentioning
confidence: 79%
“…Smoking-free policies are not enforced in public places and non-smokers cannot avoid passive smoking at such places (9), therefore, the government should enforce smoking-free policies and implement a national campaign against smoking. Our results support the involvement of primary healthcare professionals in such campaigns by providing their patients with anti-smoking advice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no previous studies have examined the prevalence of SHS exposure among children our results are consistent with many of existing literature in this field. A study in Jordan found that SHS exposure among nonsmoking university students was 96%, the mean hour of exposure per day was 4.64 hours, and the mean days of exposure per week were 5.14 days [19]. Another study among employed women in Jordan found that mean hour SHS exposure per day was 5.5 hours, with an average of 6 days per week [15].…”
Section: Discussionmentioning
confidence: 99%
“…Giving that this age group (6-11years) spends most of their time inside the home, and if they leave their homes they joined their parents either in the car or visiting relatives, or in the restaurants. Further, in Jordan a study about parents' attitudes toward SHS exposure found that only 17.7% of women expressed that they will not let their "visitors" smoke in their home [19], because it is not acceptable to ask visitors not to smoke. However, invite visitors to smoke is a type of good hospitality.…”
Section: Discussionmentioning
confidence: 99%